O pojęciu handlu - Szpaderski, Andrzej (Wydział Prawa i Administracji UAM, 1968)
The concept of trade has been considered in this paper mainly because of the aim of existance and activity of this discipline of economy. But simultaneously there are other elements of this concept which ought to be considered e.g. the subject and the sphere of activity. The entire concept of the purpose of trade is confined in two basic criteria i.e. profitableness of the enterprise and the needs of the community. Some concepts take an intermediate position in this distribution. Definitions disposed to answer the first criteria regard trade as the professional purchase of economic goods for the purpose of selling to achieve profit. In this way the point of gravity in the commercial activity moves from the activity of exchange to the flow of benefits in the form of merchant's profit. The concept that the problem of the purpose of trade can be solved on the grounds of profit remains in close contact with the principle accepted in capitalistic economy in running an enterprise. This concept of purpose can not explain the social and economic role of trade. The universalistic concepts represent a totally different opinion. By replacing the narrow meaning of enterprise by the broader meaning of the needs of the community the aims of these concepts change from the pursuit of profit to the method of procedure. The social functions of trade show distinctly the concepts of socialistic trade. Since numerous definitions of trade based on social grounds stress variously the meaning of different exchangeable functions and do not make its purpose precise, the following definition has been proposed in this paper: Trade is the professional mediation in the exchange of goods accomplished by means of purchase deed and bill of sale depending on association and adjustment of the aims of market methods dictated by the bidders and the receivers of goods, for the purpose of optimalization of meeting the demand for consumptive and industrial goods, and minimalization of the time of transactions. The salient characteristic of this definition is, that it joins and combines all positive points of definitions of concept of trade applied before. It results also from the apparent contemporary level and developing tendency in this of materialistic culture of industrialized communities.
The Concept of Trade